Transient stability analysis of IEEE 57-bus test case system using Dynamic Computation for Power Systems (DCPS) / Mohamad Farid Adnan - Adnan, Mohamad Farid (2012)
This paper is about Transient Stability Analysis of IEEE 57-Bus Test Case System by using Dynamic Computation for Power System (DCPS). Basically, the program is capable for easy extension and able to managed system up to 1000 buses and 250 generators rather than the other expansive software. In this Power System Transient Stability analysis, there are several buses have been identified as a fault buses. All of these fault buses have been analyzed based on critical clearing time (TCCT) on the stability of the system and the effect of the distance from swing bus (Bus 1) to faulty buses by using Modified Euler's method. The stability of the system has been obtained based plotted graphs obtained in term of terminal voltage, machine rotor angle, and machine speed.